Pengembangan Komposit Dari Karet Ebonit Dengan Penguat Serat Rami Untuk Bahan Komponen Otomotif Penutup Spion Sepeda Motor - Altari, Syaifa Maulana (2016)
The aim of this study. Knowing the influence of variations in immersion time with NaOH 5% against the single fiber tensile strength, in addition to determine the tensile strength, Izod impact, and violence on the variation of fiber flax 0 phr, 20 phr and 40 phr of the composite bermatrik ebonite. Examining the type of fault is generated by the tensile test and Izod impact. Manufacture of composite materials used are flax fibers which have varied immersion 5% NaOH for 0 hours, 2 hours, 4 hours and 6 hours, with a single pull fiber testing standards of ASTM D 3379-75. In the manufacture of composite ebonite berpenguat flax fibers with fiber 0 variations phr, 20 phr and 40 phr. Testing composites using ASTM D 638-02 for tensile test, ASTM D 256-00 for Izod impact testing, ISO 0778: 2009 for the hardness test, and macro photos. The results obtained by the tensile strength of the highest average at 5% variation NaOH soaking for 2 hours is 574.031 MPa. In the composite ebonite highest voltage the average obtained in ebonite with hemp fiber 20 phr namely 6.154 MPa, the price impact the highest average on the composite ebony flax fibers 40 phr 1.499 J / mm2, and Violence highest average on composite ebonite without fiber that is 91.333 scale shore A. Based on the fracture Izod impact and tensile testing type of fault that occurred is the fault of clay.